2016
DOI: 10.21111/at-tadib.v11i2.778
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Sains Berbasis Agama untuk Membangun Hidup Sehat

Abstract: Term of halalan in the religion means allowed, whereas in the science means healthy. Conservative aspect of faith-based on science education provide an explanation of the blood from the values of religion and science. From the religious point, blood (ad-dam) was haram consumed, while science explains that the consumption of blood is harmful to health. The scientific information can help us understand the secret dimension (hikmah) prohibition of the blood, that the Lord of Maintaining His servants. Role of scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Indonesia, its issue also attracts many scholars. Darda (2016) analysed the integration of religion and science historically. Meanwhile, the other scholars focused on its practice in education (Abidin 2017;Arifudin 2017;Darmalaksana 2021;Fauzi 2017;Fiteriani 2014;Hidayat 2015;Nugraha 2020;Putra 2020;Rafiq 2017;Wartini 2015).…”
Section: Contributionmentioning
confidence: 99%
“…In Indonesia, its issue also attracts many scholars. Darda (2016) analysed the integration of religion and science historically. Meanwhile, the other scholars focused on its practice in education (Abidin 2017;Arifudin 2017;Darmalaksana 2021;Fauzi 2017;Fiteriani 2014;Hidayat 2015;Nugraha 2020;Putra 2020;Rafiq 2017;Wartini 2015).…”
Section: Contributionmentioning
confidence: 99%
“…36 These sciences are only different epistemologically or how to reach them, but it is believed that they all come from one source; God who is omniscient. That's why, Darda (2016), found that every field of science must complement each other, touch and take benefits from each other so that access to an invention is more diverse and richer.…”
Section: The Wahdatul 'Ulum Theory (The Integration Of Science)mentioning
confidence: 99%